Bulk Segregant Analysis Reveals the Genetic Basis of a Natural Trait Variation in Fission Yeast. (27th November 2015) - Hu, Wen; Suo, Fang; Du, Li-Lin
Abstract: Although the fission yeast Schizosaccharomyces pombe is a well-established model organism, studies of natural trait variations in this species remain limited. To assess the feasibility of segregant-pool-based mapping of phenotype-causing genes in natural strains of fission yeast, we investigated the cause of a maltose utilization defect (Mal - ) of the S. pombe strain CBS5557 (originally known as Schizosaccharomyces malidevorans ). Analyzing the genome sequence of CBS5557 revealed 955 nonconservative missense substitutions, and 61 potential loss-of-function variants including 47 frameshift indels, 13 early stop codons, and 1 splice site mutation. As a side benefit, our analysis confirmed 146 sequence errors in the reference genome and improved annotations of 27 genes. We applied bulk segregant analysis to map the causal locus of the Mal - phenotype. Through sequencing the segregant pools derived from a cross between CBS5557 and the laboratory strain, we located the locus to within a 2.23-Mb chromosome I inversion found in most S. pombe isolates including CBS5557. To map genes within the inversion region that occupies 18% of the genome, we created a laboratory strain containing the same inversion. Analyzing segregants from a cross between CBS5557 and the inversion-containing laboratory strain narrowed down the locus to a 200-kb interval and led us to identify agl1, which suffers a 5-bp deletion in CBS5557, as the causal gene. Interestingly, loss of agl1 through a 34-kb deletion underlies the Mal - phenotype of another S. pombe strain CGMCC2.1628. This work adapts and validates the bulk segregant analysis method for uncovering trait-gene relationship in natural fission yeast strains.